The Use of Technology in the Management of Orthodontic Treatment-Related Pain - Anand Marya; Adith Venugopal (Pain Research and Management)
Orthodontic pain is one of the negatives associated with fixed orthodontic treatment that cannot be avoided. This pain usually comes around the wire placement period and gradually decreases once the endogenous analgesic mechanisms start functioning. Over the years, several treatment modalities have been utilized for relief from orthodontic pain, and these include mechanical, behavior modification, and pharmacological methods. However, in the last decade, there are several newer methods employing the use of technology that have come up and are being used for alleviating pain. From computerized indirect bonding to virtual treatment planning, technology has slowly become a vital part of an orthodontist’s repertoire. The digital age is here, and orthodontics must embrace the use of technology to help improve the quality of life of patients.